IMPLEMENTATIONS OF FORENSIC DENTISTRY IN CRIMINAL INVESTIGATIONS: REVIEW ARTICLE - Al-Sarhani, Mansour (European Scientific Journal, ESJ, 2014)
This review article was conducted to show the implications of forensic dentistry in criminal investigations. The idea of the present study depends on increased awareness of the importance of forensic dentistry implication in identification of identity of suspicious and victims. These implications included examining elements of oral cavity such as teeth, periodontal tissues and anatomical structures. Teeth are the remaining issues that contain genetic material and remain unaffected for a long time. We also denoted to the potential use of bite mark analysis. Bite analysis is considered a good physical evidence which serve for identification of both victims and criminals. Teeth are used as a weapon that mainly used by victims to defend themselves against attackers. It can also be used by attackers to express their dominance over victims. We also reviewed advancements in using molecular biology techniques in forensic dentistry. Tooth is considered a good source for genetic material since tooth resists severe adverse conditions when the body is destructed. Finally, we pointed to some software programs used in forensic dentistry to help in identification of dead persons particularly in massive conditions. Taken together, forensic dentistry has become one of valuable tools worldwide to be used in identification processes and we recommend to use national databases to be used for comparison purposes as the case of fingerprints.